Measuring accessibility as a capability: theoretical and practical implications for transport justice - Ferreira, Lucas Sousa (2023)
Although accessibility is recognised as a pivotal determinant of social equity, its evaluation is often oversimplified by neglecting heterogeneities and essential factors beyond travel time. Transport justice literature has emphasised the role of the capability approach (CA) in treating individual aspects in accessibility analysis, however, few studies have built practical applications in the field. For instance, no study has explored how individual income, a core determinant of access, directly impacts accessibility, especially in the CA context. Even when considering income, studies often focus on aggregate approaches that are based on averages. These approaches may overestimate the accessibility of the least advantaged and bias equity analyses by underestimating poverty and inequality. This lack of studies is a result of the dearth of both theoretical and operational methodological approaches on accessibility-as-capability measurement. This dissertation aims to address these issues. We built on CA a comprehensive framework for accessibility measure development by observing individuals’ heterogeneities in access. What should be the guiding design for shaping an accessibility-as-capability measure? To answer this question, we developed a three-fold framework. First, we propose a formal definition for accessibility-as-capability measures. Second, we propose specific criteria to ensure compatibility among CA, accessibility measures, and justice assessment purposes. Third, we propose an operational pathway to integrate CA into the development of accessibility metrics, thereby contributing to advancing the discourse on transport justice. We advance CA operationalisation in the accessibility domain by building on the framework an accessibility-as-capability measure, in addition to a method of application. This measure adapts a cumulative opportunity measure (COM) to account for individual heterogeneity. We applied it in a case study regarding the job accessibility of the head of household in Fortaleza (Brazil) and analysed its implications on inequality and poverty analysis. The results revealed that, without accounting for individual constraints in accessibility measures, such as income and education, inequality in accessibility, as measured by the Palma ratio, might be underestimated by more than three times. From a sufficiency perspective, individuals’ constraints inclusion also substantially raises the poverty rate in terms of accessibility, revealing up to 92.5% more people living in chronic poverty when compared to COM measure. This finding reveals a two-fold implication. First, by not considering individual constraints, we do not know the real conditions of deprivation faced by the population regarding access to opportunities. Second, this bias in inequality and deprivation analyses could result in policies that do not properly address injustices. These results demonstrate how not accounting for individuals’ constraints on access could substantially change justice assessment from both equality and sufficiency perspectives and highlight the need for advancements in transport justice measurement and evaluation.